Reclamation of nutrients from kenaf retted wastewater using modified ultrafiltration membrane / Nabilah Huda Abdul Halim - Abdul Halim, Nabilah Huda (2016)
Increase in demand of fiber from kenaf industry, increases the water usage for water retting. Traditional water retting method producing large amount of water in greenish color, high in suspended solids, high BOD load, the reduction of DO, high nutrient levels and non-biodegradable substances where discharge directly into watercourses triggering eutrophication in aquatic ecosystem. The aim of this research is to formulate and fabricate membrane for reclamation of nutrients from kenaf retted wastewater. The flat-sheet Polysulfone (PSF) membrane were prepared by dry/wet phase separation technique with various Polyvinyl-pyrolidone (PVP) additive concentrations (0, 1.5, 4.8, 9.1 wt. %) and were analyzed towards morphology, flux performance and nutrients reclamation to verify the potential for reclamation of nutrient from kenaf retted wastewater (KRW). It is observed that the NaCl rejection was increased, while membrane flux was decreased with the increase in PSF concentration. Results from modified membrane using PVP at different concentration obtained the inconsistent water flux results. These experimental results suggest that the modified PSF ultrafiltration membrane which is added of 1.5 wt. % PVP together with 14.8 wt. % PSF/ 83.7 wt. % DMAC has high flux, obtained close to 50% NaCl rejection and it successfully rejects the solute solution with molecular weight 100 kDa in 90%. This membrane also has high resistance to pressure 5 bar in 180 minutes. PVP₁.₅ was efficiently reclaiming more than 90% of total nitrogen (TN), near to 90% of total phosphorus (TP), above 85% of potassium (K) from KRW. The finding obtained indicated that modified membrane has a successful potential for nutrients reclamation of kenaf retted wastewater.